Contratos privados da administração pública: uma análise do regime jurídico aplicável - Carvalhaes Neto, Hayden Eduardo (Universidade de São Paulo, 2011)
A celebração de negócios jurídicos é fundamental para a Administração Pública. Sem ela, não só sua interação com a sociedade seria precária, como também não conseguiria cumprir com a maior parte dos princípios que regem seu regime jurídico, pois não se mostra autossuficiente. Para formalizar tais negócios jurídicos, o instrumento utilizado é o contrato. Parte da doutrina defende que tais instrumentos não se enquadram adequadamente no conceito de contrato por conta das peculiaridades que os cingem quando uma das partes pertence à Administração Pública ou está a exercer função que lhe foi delegada pelo Poder Público. De outro lado, aqueles que concordam com a classificação desses instrumentos como contratos dividem-se entre os que acreditam existir um regime jurídico único para todos os contratos da Administração Pública e aqueles que defendem a existência de duas modalidades de contratos: os contratos administrativos, regidos predominantemente pelo direito público, e os contratos privados da Administração Pública, que, tendo como objeto negócios jurídicos característicos da vida privada, são regidos predominantemente pelo direito privado. Somos partidários desta última corrente e, diante da escassa literatura pátria sobre os contratos privados da Administração Pública, nos propomos a analisá-los mais detidamente no presente estudo. Assim, dividimos este trabalho em cinco capítulos. No primeiro deles, apresentaremos nossas considerações iniciais sobre a matéria, fornecendo um apanhado do que a doutrina nacional e estrangeira já produziu sobre o assunto e de como se dividem as opiniões. Tendo em vista que os contratos regidos primordialmente pelo direito privado apresentam grande parte dos traços dos contratos privados, no segundo capítulo analisaremos as características mais relevantes das cláusulas típicas de direito público que integram os contratos administrativos. O terceiro capítulo, por sua vez, é dedicado à verificação da legislação brasileira e os respectivos dispositivos normativos pertinentes aos contratos privados da Administração Pública. No quarto capítulo nos debruçaremos sobre as decisões jurisprudenciais estrangeiras que marcaram o início da distinção entre as duas modalidades de contratos da Administração Pública e no quinto capítulo apresentaremos nossas conclusões, conjuntamente com algumas sugestões que acreditamos sejam pertinentes ao aperfeiçoamento do tratamento da matéria no Brasil. The execution of legal businesses is essential for the Public Administration. Without it, not only its interaction with society would be precarious, but also could not comply with most of the principles governing their legal regime, as it is not show selfsufficient. In order to formalize such legal transactions, the instrument to used is the agreement. Part of the doctrine sustains that such instruments do not fit properly on the concept of agreement because of its peculiarities when one of the parties belongs to the Public Administration or is exercising function that has been delegated by the Public Power. On the other hand, those who agree with the classification of such instruments as agreements are divided between those who believe that there is a single legal regime for all the agreements executed by the Public Administration and those who advocate the existence of two "modalities" of agreements: the administrative agreements, predominantly governed by public law, and private agreements of the Public Administration, which having as subject legal businesses that are typical of the private life, are governed mainly by private law. We agree with this latter view, and because of the scarce literature on private agreements of the Public Administration, we propose to examine them more closely in this study. We have divided this paper into five chapters. In the first one, we will present our initial thoughts on the subject, providing an overview of what the national and foreign doctrine has produced on the subject and how the opinions are divided. Given that agreements governed by private law primarily present most of the characteristics of private agreements, in the second chapter we will analyze the most relevant characteristics of the typical clauses that integrate the administrative agreements. The third chapter, on its turn, is devoted to the verification of the Brazilian legislation and the respective applicable normative provisions pertaining to the private agreements of the Public Administration. In the fourth chapter we will lean over the foreign court decisions that became the landmarks of the beginning of the distinction between the two modalities of agreements of the Public Administration and in the fifth chapter we will present our findings, together with some suggestions that we believe are relevant to improving the handling of this matter in Brazil
Keywords: Administrative agreements; Administrative law; Administração publica; Agreements; BID; Contrato administrativo; Exorbitant clauses; Legal business; Licitação; Prerogatives; Private agreements; Public administration

Dynamiques paysannes, souveraineté alimentaire et marché mondial des produits agricoles : exemple du Sénégal - Diop, Amadou Makhourédia (Institut National Polytechnique de Toulouse, 2011)
Comme dans presque tous les pays d'Afrique subsaharienne, la majorité de la population sénégalaise est rurale. Elle vit de l'agriculture ou d'activités qui en dépendent. Paradoxalement les investissements publics dans le secteur agricole restent très faibles, alors que l'insécurité alimentaire progresse. Pour faire face aux problèmes alimentaires, les pouvoirs publics multiplient les annonces de politiques agricoles, qui ne sont presque jamais suivies d'effets, parce que ne reposant pas sur des études précises et rigoureuses. Dans ce contexte, nous avons cherché à comprendre les stratégies développées par la petite paysannerie, les dynamiques qui animent les exploitations agricoles familiales pour faire reculer l'insécurité alimentaire en milieu rural, et dans quelle mesure celles-ci peuvent contribuer à la souveraineté alimentaire du Sénégal. Cette question appelle celle de l'accès à une nourriture suffisante et celle de sa production. Ainsi, à travers notre étude que nous avons intitulée « Dynamiques paysannes, souveraineté alimentaire et marché mondial des produits agricoles : l'exemple du Sénégal », nous cherchons à répondre à une série de questions : 1. Comment les paysans sénégalais produisent-ils les biens nécessaires à l'alimentation et l'entretien de leur famille ? 2. Comment les paysans sénégalais sont-ils organisés autour des questions de la vie rurale ? 3. Quelle est l'influence du marché mondial de produits agricoles et de ses règles établies par l'Organisation mondiale du commerce (OMC), sur la disponibilité et l'accès aux produits alimentaires ? De quelle façon les biens alimentaires importés concurrencent-ils la culture de biens agricoles qu'il est possible de produire localement ? Nous avons ainsi consacré une première partie de notre étude au procès de production et à son évolution. En dehors des conditions climatiques, le contrôle effectif par les paysans, des moyens de production et de la tenure foncière, détermine en grande partie, les volumes de biens agricoles et alimentaires produits, ainsi que leur accès. Dans une seconde partie, nous avons analysé l'émergence et l'évolution des modes d'organisation paysanne et examiné leur influence sur la satisfaction des besoins alimentaires et les orientations des politiques publiques en matière agricole. Enfin, dans une troisième partie, nous avons essayé de mesurer l'impact des règles du commerce international sur les productions locales de biens agricoles et alimentaires. Ce travail nous a permis de tirer un certain nombre de conclusions. La majorité des paysans du Sénégal ne parvient plus à produire le volume d'aliments de base nécessaires pour nourrir et entretenir leur famille. Les moyens de production ont relativement peu évolué au cours des dernières décennies, même si la culture attelée et l'introduction de nouveaux matériels ont considérablement amélioré les conditions de production et diminué la pénibilité du travail. L'outil de production s'est dégradé et ce qu'il en reste ne survit que grâce à l'habileté des forgerons ruraux. La recherche agronomique a permis d'obtenir des variétés homologuées de semences adaptées aux conditions pédologiques et climatiques. Mais elle demeure inefficace en ce sens que les moyens pour appliquer concrètement ses résultats sont absents et les paysans n'ont aucune maîtrise sur elle. Sur le plan du commerce international des produits agricoles, la faiblesse du Tarif extérieur commun (TEC) de la CEDEAO a eu pour conséquence l'augmentation des volumes d'importations de biens qui peuvent être produits localement. Les règles de l'OMC basées sur une conception ultralibérale du marché portent davantage préjudice aux produits agricoles et alimentaires de l'Afrique de l'Ouest. Sur un plan plus global, et à défaut de sortir l'agriculture des accords de l'OMC, il est possible de réclamer avec la CEDEAO, la mise en place d'un autre Accord sur l'agriculture qui redéfinirait le dumping de manière à protéger les pays les plus vulnérables. As in almost all SSA countries, the majority of the Senegalese population is rural. They earn their livelihoods from agriculture or activities that depend on it. Paradoxically, the public investment in agriculture remains very low, while food insecurity is progressing. To deal with food problems, the government multiplies announcements of agricultural policies, which are almost never followed up, because not based on specific and rigorous studies. Instead of policies, there are mostly management strategies cyclical food crises. In this context, we have sought to understand the strategies developed by the peasantry, the dynamics that drive family farms to reduce food insecurity in rural areas, and to what extent they can contribute to food sovereignty Senegal. This question calls for that of access to adequate food and that of its production. Thus, through our study we have entitled "Farming dynamics, food sovereignty and global market for agricultural products: the example of Senegal”, we try to answer a series of questions: 1. How do Senegalese farmers produce the goods needed to feed and care for their family? 2. How are Senegalese farmers organized around issues of rural life? 3. What is the influence of the world market of agricultural products and its rules established by the World Trade Organization (WTO) on the availability of and access to food? How do imported goods compete with food products that can be produced locally? We have devoted the first part of our study to the production process and its evolution. Apart from weather conditions, effective control by farmers of means of production and land tenure, largely determines the volumes of agricultural and food products as well as their access. The second part analyzes the emergence and evolution of modes of peasant organization and discusses their influence on the satisfaction of food needs and directions of public policy in agriculture. Finally, in the third part, we have tried to measure the impact of international trade rules on local production of agricultural goods and foodstuffs. This work has enabled us to draw some conclusions. The majority of farmers in Senegal can no longer produce the amount of basic foods needed to feed and support their families. The means of production have changed relatively little in recent decades. The production tool has deteriorated and what is left survives only thanks to the ability of rural blacksmiths. Research in agriculture has yielded certified seed varieties adapted to soil and climatic conditions. But it remains ineffective in that the means for concretely applying its results are absent and the peasants have no control over it. The question of land remains subject to trial and error due to its complexity, traditional beliefs and practices in this area do not yet seem ready to give way to modern rules, or if necessary, adapt to them. More and more severe conditions felt primarily in the food sector have highlighted the capacity of the peasantry to adapt. For each new situation causing additional problems, novel solutions are devised and implemented by farmers, enabling them to adapt in an unexpected manner. Farmers' ability to take charge of their own concerns were highlighted by the emergence of organizations, groups, associations and unions throughout the rural areas of Senegal. As far as international trade in agricultural products is concerned, the weakness of the Common External Tariff (CET) of ECOWAS has resulted in increased volumes of imports of goods that can be produced locally. WTO rules, based on an ultra-liberal conception of the market, are more detrimental to West African agricultural and food products. More globally, unless agriculture is removed from WTO agreements, it is possible to claim with ECOWAS, the implementation of another agreement on agriculture that would redefine dumping so as to protect the most vulnerable countries.
Keywords: Agricultural policy; Exploitation familiale; Family farms; Food security; Land tenure; Marchés agricoles; Market of agricultural products; Organisations paysannes; Peasant organizations; Politique agricole; Sécurité alimentaire; Tenure foncière

Hukuk sosyolojisi açısından vahiy döneminde ticari hayat - Baysa, Hüseyin (Ondokuz Mayıs Üniversitesi, 2011)
Modern dönemde ticarî hayatta ortaya çıkan mübadele yöntemlerini İslâm ticaret hukuku açısından değerlendirebilmek ve İslâm'ın ticarî alandaki temel ilkelerine aykırı işlemlere alternatif yöntemler üretebilmek için öncelikle vahiy dönemindeki ticaret hukukunu tespit etmek gerekmektedir. Vahiy dönemindeki ticaret hukukunun sağlıklı bir şekilde anlaşılabilmesi ise dönemin ticarî kurallarının sosyolojik açıdan incelenmesini zorunlu kılmaktadır. Bu amaçla yapılan bu araştırmada ulaşılan sonuçları kısaca şu şekilde ifade etmek mümkündür:Cahiliye döneminde Hicaz bölgesinde sosyal hayat, bölgenin coğrafî yapısı ile dönemin siyasî ve dinî şartları etkisi altında sürdürülmüştür. Yeni bir yaşam biçiminin hedeflendiği vahiy döneminde toplumsal hayatın bütün ünitelerinde değişikliğe gidilmiş, Hicazlılar'ın iktisadî tecrübe ve ihtiyaçları göz önünde bulundurularak yeni bir ticaret hukuku oluşturulmuştur. Mekke devrinde, Hz. Peygamber kanun koyup uygulayacak siyasî güce sahip olmadığı için, hayatın diğer alanlarında olduğu gibi ticaret hukuku alanında da temel ahlâkî değerler müslüman tebaaya benimsetilmeye çalışılmakla yetinilmiştir. Hicretten sonra Medine'de siyasî ve askerî bakımdan yeterli güce kavuşulunca ekonomik sisteme müdahale edilmeye başlanmıştır. Bir önceki dönemden devralınan ticarî kurum ve işlemler adalet eksenli yeni hukukî ve ahlâkî kurallara göre değerlendirilmeye tabi tutulmuştur. Ticaret hayatında yapılan değişiklikler içtimaî kurallara uygun bir şekilde gerçekleştirilmiştir. Yeni hukukî düzenlemelerin kargaşaya meydan vermemesi için gerekli görülen konularda tedricî yöntem uygulanmış ve alternatif uygulamalar devreye sokulmuştur. Öte yandan toplumsal yapıyı oluşturan diğer kurumlarda gerçekleştirilen değişiklikler de yeni ticaret hukukunun kolaylıkla topluma mal edilmesinde oldukça etkili olmuştur. Occurring in the commercial life of modern methods of exchange, to assess in terms of commercial law of Islam, and contrary to the fundamental principles of commercial transactions in the field of Islam in order to produce alternative methods, primarily trade law to determine the required period of revelation. Revelation during the period of commercial law in a healthy way to understand the rules of trade requires a review of the sociological perspective. For this purpose, the results achieved in this study, it is possible to briefly stated as follows:The period of ignorance of social life in the Hijaz, the region's geographical structure and the period continued under the influence of political and religious conditions. Revelation in a new way of life, social life aimed to change all the units were made, considering the economic needs of the people of Hijaz experience and created a new trade law. Mecca during the reign of the Prophet put the law does not have the power to implement the political, as in other areas of life in the field of commercial law to teach basic moral values were muslims. After the migration, the strength is reached Medina, the political and military respects, the economic system started to intervene. Commercial institutions and processes inherited from the previous period, according to the rules of justice-oriented evaluation has been subject to new legal and moral. Changes to trade in his life was carried out in accordance with social rules. New legal challenge to prevent confusion in the arrangements, gradual method is applied to matters deemed necessary and alternative practices were introduced. On the other hand, changes in social structure in the new trade law is easily performed by other institutions in society to be the goods have been quite effective.
Keywords: Cahiliye Dönemi; Commercial law; Commercial life; Hedjaz; Hicaz; Hukuk sosyolojisi; Islam; Jahiliyye Period; Law sociology; Socio-cultural structure; Socio-economic life; Sosyoekonomik hayat; Sosyokültürel yapı; Ticaret; Ticaret hukuku; Ticari hayat; Trade; İslamiyet

South African anti-dumping law and practice : a juridical and comparative analysis of procedural and substantive issues - Sibanda, Omphemetse Stephen (North-West University, 2011)
This thesis addresses issues of anti-dumping law and practice from a critical and juridical analysis position. In particular, the thesis seeks to determine whether the South African anti-dumping regime is compliant with the anti-dumping regime of the World Trade Organization (hereafter WTO), and to consider possible solutions for addressing instances where the South African law is not WTO compatible. The thesis departs from the hypothesis that the WTO merely requires functional equivalence of the implementation of national legislation on anti-dumping, and not the verbatim adoption of WTO jurisprudence and relevant provisions of the Agreement on the Implementation of Article VI of the General Agreement on Tariffs and Trade of 1994 (hereafter URAA), into the legislation of State Parties. Some of the provisions of the URAA are not completely clear, and are cast in convoluted and complicated technical jargon, leaving loopholes that may be justifiably exploited by State Parties. The study in this thesis was achieved through the critical analysis of legislation and relevant legal documents, case law and contemporary literature. The primary research paradigm used in this study is interpretive and analytical, which is the same as qualitative research methodology. The legal comparative research method, with a historical component, also played an important role in this study. The literature study undertaken and the critical analyses made of the South African anti-dumping regime show mixed findings. The South African antidumping regime was found to have both positive aspects and problematic aspects when compared with WTO regulations. Some of the critical areas of the South African anti-dumping regime are WTO compatible whilst others are not. In some areas the South African anti-dumping regime has adopted functionally equivalent provisions to the provisions of the WTO law. However, the practice of the International Trade Administration Commission (ITAC) is sometimes fraught with inconsistencies. The compatibility of the South African anti-dumping system with the WTO regime came close to being examined by the WTO on 1 April 1999 in the dispute of South Africa - Anti-dumping Duties on the Import of Certain Pharmaceutical Products from India based on allegations that the method for calculating normal value used by the ITAC was found to be inconsistent with the URAA. Similarly, the conformity of the procedures and findings of the International Trade and Administration Act (ITAA) in anti-dumping cases came under attack in the cases of Algorax v The International Trade Administration Commission and others, and Scaw v The International Trade Administration Commission and others, respectively. Finally, the thesis ends with recommendations in response to the challenges identified and key submissions made throughout the analysis. Key recommendations include the broadening of the concept of interested parties to include registered trade unions and trade union federations; introducing an explicit and mandatory "public Interests" provision to ensure that South Africa's anti-dumping administration is free from political trappings in the form of the involvement of the Minister of Trade and Industry; introducing the new section 31 bis of the ADR in order to allow the initiation of anti-dumping petitions by a registered trade union or trade union federation; providing procedural guidelines for self-initiation of anti-dumping petitions by the ITAC; increasing transparency in anti-dumping proceedings and enquires; setting realistic time-lines for all anti-dumping processes and ensuring compliance with the same; improving the institutional and functional capacity of the ITAC; amending section 18.3 of the ADR to allow search and seizure operations pursuant to the provisions of the Criminal Procedure Act 51 of 1977 and the Customs Act; having a clear provision on verification visits confidentiality and a clear provision on producer knowledge; introducing a clear provision in the ADR dealing explicitly with zeroing pursuant to Article 2.4.3 (ii) of URAA; and the introduction of duty refund procedures. It is hoped that the recommendations made in this thesis, which are in the form of suggested legislative interventions required to upgrade certain areas of South African anti-dumping law and practice to be fully WTO compliant, will influence the introduction of suitably crafted anti-dumping legislation in South Africa. It is further hoped that the thesis will become an invaluable source of information for practitioners and students, and a critical source on the best practice for the imposition and implementation of anti-dumping measures. Moreover, the thesis will add to the body of academic writing on South African anti-dumping law.
Keywords: Antidumping duties; Dumping (International trade); South Africa